Injury Epidemiology and Time Lost From Participation in Women's NCAA Division I Indoor Versus Beach Volleyball Players. Issue 4 (23rd April 2021) - Juhan, Tristan; Bolia, Ioanna K.; Kang, Hyunwoo P.; Homere, Andrew; Romano, Russ; Tibone, James E.; Gamradt, Seth C.; Weber, Alexander E.
Background: Beach volleyball officially became a National Collegiate Athletic Association (NCAA) Division I sport in 2015-2016. Few studies have examined the epidemiology of injuries in indoor versus beach volleyball in NCAA Division I athletes. Purpose: To compare the epidemiology of injuries and time lost from participation between female NCAA Division I athletes who participate in indoor versus beach volleyball. Study Design: Cohort study; Level of evidence, 3. Methods: Injury surveillance data (2003-2020) were obtained using an institutional database for all NCAA Division I women's beach or indoor volleyball athletes. The total injury rate was expressed per 1000 hours played. The injury rate per body site was calculated by dividing the number of injuries in each body region by the total number of injuries. The frequency of injury per body site was also expressed as number of injuries per 1000 hours of practice or number of injuries per 1000 hours of game. The injury rate (total and per body site) and time lost from participation were compared between indoor and beach volleyball athletes. Results: Participants were 161 female NCAA Division I volleyball athletes (53 beach volleyball and 108 indoor volleyball athletes). In total, 974 injuries were recorded: 170 in beach volleyball and 804 in indoor volleyball. The injury rates for beach versus indoor volleyball were 1.8 versus 5.3 injuries per 1000 hours played ( P < .0001). Indoor volleyball athletes had significantly higher injury rates compared with beach volleyball players for concussion (7.5% vs 6.5%; P < .0001) and knee injury (16.7% vs 7.6%; P = .0004); however, the rate of abdominal muscle injury was significantly higher in beach versus indoor volleyball (11.8% vs 4.7%; P = .0008). Time lost from sport participation was significantly longer in beach versus indoor volleyball for knee (24 vs 11 days; P = .047), low back (25 vs 17 days; P = .0009), and shoulder (52 vs 28 days; P = .001) injuries. Conclusion: Based on this study, injury was more likely to occur in indoor compared with beach volleyball. Sport-related concussion and knee injuries were more common in indoor volleyball, but the rate of abdominal muscle injury was higher in beach volleyball. Beach volleyball players needed longer time to recover after injuries to the knee, low back, and shoulder.